2019
DOI: 10.1039/c8tc04708a
|View full text |Cite
|
Sign up to set email alerts
|

Dual nature of exciplexes: exciplex-forming properties of carbazole and fluorene hybrid trimers

Abstract: Two exciplexes were detected for the first time for the known exciplex-forming system consisting of electron donating 1,3-bis(N-carbazolyl)benzene and electron accepting 2,4,6-tris[3-(diphenylphosphinyl)phenyl]-1,3,5-triazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In contrast, in protic solvents such as alcohols and H 2 O, no long‐wavelength fluorescence was observed, and in aprotic solvents such as THF and 1,4‐dioxane, long‐wavelength fluorescence was detected. The spectral changes observed in all the solvents strongly suggest the formation of an exciplex between 15Nap‐Cl and TEA. A schematic of the PET and the formation of the exciplex is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in protic solvents such as alcohols and H 2 O, no long‐wavelength fluorescence was observed, and in aprotic solvents such as THF and 1,4‐dioxane, long‐wavelength fluorescence was detected. The spectral changes observed in all the solvents strongly suggest the formation of an exciplex between 15Nap‐Cl and TEA. A schematic of the PET and the formation of the exciplex is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the evidently improved Φ PL of DBT-SADF:PO-T2T:CDBP is actually ascribed to the better upconversion of triplet excitons with three RISC channels and prove the feasibility of our strategy to improve the exciton utilization of exciplex emitters. Moreover, to the best of our knowledge, this is the first report with an EQE over 20% for the OLEDs based on exciplex emitters at room temperature (Figure 4; Table S2, Supporting Information), [1,2,[4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21]30,31,[46][47][48] thus our novel strategy of tricomponent exciplexes will provide a valuable approach for further development of exciplex emitters. As the mixing ratios of exciplexes would change their charge balance and affect the device performance, [13,14] the carrier transporting properties of four exciplexes were carefully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The lower-energy exciplex could be beneficial due to the energy transfer between two exciplexes. [1,2,[4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21]30,31,[46][47][48] The outstanding performance of the DBT-SADF:PO-T2T:CDBP-based OLEDs not only demonstrates that introducing multiple RISC channels can effectively improve the exciton utilization of exciplex emitters, but also proves the superiority of our novel tricomponent exciplex strategy for further development of exciplex emitters. According to our novel strategy, two tricomponent exciplex emitters, 13AB ((1,3-bis(9,9dimethylacridin)) benzene):PO-T2T ((1,3,5-triazine-2,4,6-triyl) tris(benzene-3,1-diyl) tris(diphenylphosphine oxide)):CDBP (4,4′-bis(9-carbazolyl)-2,2′-dimethylbiphenyl) and DBT-SADF Energy transfer diagrams of the conventional bicomponent TADF exciplexes, TADF-assistant bicomponent TADF exciplexes, and novel tricomponent TADF exciplexes (blue: conventional constituent material, orange: single-molecule TADF emitter).…”
Section: Introductionmentioning
confidence: 99%
“…These defects are the cause of the reduction in luminance efficiency and device stability. Several authors have reported that they reduced these defects through thermal annealing, thus effectively improved the stability of the OLEDs devices . Besides, it was reported that the proper thermal annealing condition of the emissive layer resulted in a denser film with suitable packing and interplanar distance of the molecules, leading to better carrier mobility and higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that they reduced these defects through thermal annealing, thus effectively improved the stability of the OLEDs devices. [27,28] Besides, it was reported that the proper thermal annealing condition of the emissive layer resulted in a denser film with suitable packing and interplanar distance of the molecules, [29] leading to better carrier mobility [30] and higher efficiency. Such a better molecular orientation in the emissive layer, the optimized hostguest interaction [31,32] could be realized to achieve better efficiency.…”
Section: Introductionmentioning
confidence: 99%